Utilizing Augmented Reality Technology for Teaching Aid Tools based on Model-based Learning (AR-MB) - Nor Azhar, Ahmad; Rahmah, Mokhtar; Roslina, Abd. Hamid; Fauziah, Zainuddin; Emi Syakilah, Takhta (UTM Academic Leadership (UTMLead), 2016)
Highlights: The success of model-based learning requires extensive preparations and the adoption of appropriate strategies. This is because object visualization plays a crucial role for this type of learning with student engagement in self-imagination being significantly reduced. Therefore, a prototype was developed using the Augmented Reality-Model-Based (AR-MB) framework to test its effectiveness in providing a better learning tool to students. A study involving a group of university students, who were enrolled in the Ethnic Relation subject was conducted to enhance their understanding of the Iranuns – a Sabahan ethnic group. The study concluded that 86% of students agree that AR can enhance their understanding of the related subject matter. Hence, the prototype proves to be a successful model that could also be implemented in other subjects. Future applications include the adaptation of a developmental framework for architectural modelling courses.